Capital de risco no Brasil: uma análise dos fundos de investimento em participações como estrutura de governança - Santos, érico Lopes dos (2007)
An analysis of the Brazilian corporate legislation, with particular emphasis on the governance structures and agency problems of investment funds and corporations (Sociedades Anônimas), was undertaken in order to make a comparison between these legal forms in regard to their possible use in private equity and venture capital investment. This comparison was mainly qualitative, as quantitative data for the industry remains very scarce in Brazil. The by-laws of 30 Fundos de Investimento em Participações (FIP) out of a total of 33 operating in Brazil were analysed. It could be easily seen that the FIPs have widely varied characteristics due to the flexibility permitted by the legislation. In spite of some advantages perceived in the use of holding corporations or some types of investment funds other than FIPs, the overall conclusion reached was that FIPs would be in most cases the preferred structure for investment in private equity and venture capital in Brazil.